An unusual presentation of acute osteomyelitis of tibia with superficial venous thrombosis in a child - Navya Sree Veldanda; Vamshi Krishna Kondle; Rajanna Rajender Paka; Tarun Kumar Suvvari (Apollo Medicine)
Acute hematogenous osteomyelitis is the most common cause of osteomyelitis in children. It requires early diagnosis and treatment to minimize the risk of sequela of growth disturbances and deformity. We present a case of an unusual presentation of osteomyelitis of the tibia with Superficial venous thrombosis in a 2½ year male child, which was 1st ever reported association. A high degree of clinical suspicion of venous thrombosis, especially in pediatrics osteomyelitis, is required, with high C-reactive protein and erythrocyte sedimentation rate levels, as the child presents insidiously.